Biodiversity and abundance of benthic macro invertebrates community of Datte-da-Talab pond, Birpur (J&K) India - Sharma, K.K; Antal, Neha; Kour, Sarbjeet; Devi, Aarti; Sharma, Vipulab (International Multidisciplinary Research Journal, 2013)
A Perennial pond "Datte Da Talab" has a dense population of benthic communities and it plays an important role in the exchange of nutrient cycles in the aquatic ecosystem. Fourteen (14) different species were identified in the present investigation belonging to three groups viz. Annelida (3 taxa), Arthropoda (8 taxa) and Mollusca (3 taxa). Arthropoda represented by Chironomus chironomus, Chironomus pupae, Pentaneura sp., Culicodes sp., Tabanus sp., Berosus sp., Paracymus sp., Hydroglyphus sp. and Canthydrus sp. The population of Mollusca was represented by Melanoides tuberculata, Physa sp. and Gyralus sp. Annelida dominated by Tubifex tubifex, Branchiura sp. and Dero digitata. Arthropoda was the dominant group among all and it constitutes 43.19 % of the total macrobenthic invertebrates collected. Mollusca were the second dominant group and contribute 38.55 % of total macrobenthic population. Whereas group Annelida was the least abundant among all and it shared 18.26 % of total macrobenthic fauna of pond. The maximum abundance of macrobenthic organisms recorded from station IV and minimum at the station I, which was 11558 and 7712 individuals/m2sediment respectively. The relative species diversity, species richness, dominance and evenness were calculated. The value of Simpson index ranged between H' = 0.48 to 0.69. The value of Shannon-Weiner index was higher (I = 1.66) at station III. Species richness in term of Maraglef's index and Menhinick's index varied between minimum valued R1= 1.08 (Station IV) to a maximum value R1 = 1.22 (Station III) and a minimum valued R2= 0.105 (Station IV) to a maximum value R2 = 0.133 (Station III) respectively. The minimum evenness value was observed at station I and maximum at station III the values being E = 0.581 and E = 0.668 respectively. The pond was investigated monthly during the year 2011-2012 for various physico-chemical parameters and macrobenthic invertebrates. Among physico-chemical parameters Depth, Transparency, pH, Water Temperature, Air Temperature, Weather conditions, Dissolved oxygen, Free carbon dioxide, Carbonates, Bicarbonates, Calcium, Magnesium, Chlorides, Phosphates, Sulphates and Nitrates were monitored which showed well marked seasonal fluctuations.